Pengaruh Cash Holdings dan Intelectual Capital Terhadap Nilai Perusahaan Dalam Perspektif Ekonomi Islam - Muhamad Wardany Anwar; Budi Suharto; Zulaikah Zulaikah; Ade Eko Setiawan (Jurnal Ilmiah Ekonomi Islam, 2023)
The value of the company is the price that prospective buyers are willing to pay if the company is sold. When a company offers its shares to the market, the value of the company will be reflected in its share price. With the increase in share prices in the market, shareholders will become more prosperous in their shareholdings. The main goal of the company is to maximize the value of the company. Maximizing the value of the company is very important for the company, because maximizing the value of the company also means maximizing the prosperity of shareholders which is the company's main goal. So that the value of the company describes how well or poorly management manages its wealth, in this case it can be seen from the measurement of financial performance obtained. Therefore, the factors that are thought to affect the value of the company include Cash Holdings and Intellectual Capital. The formulation of the problem in this study is how the influence of Cash Holdings and Intellectual Capital. The purpose of this study is to examine and analyze the effect of Cash Holdings and Intellectual Capital. In this study the method of determining the sample using purposive sampling technique. The population in this study is the Sharia Stock Index (ISSI) for the 2016-2020 period. Based on the sample selection, the sample in this study amounted to 18 data samples. The data analysis technique in this study is multiple linear regression analysis using SPSS 25 software. Based on the results of the study, it is stated that the Cash Holdings variable has a significant negative effect on firm value and Intellectual Capital has a significant positive effect on firm value.